Robust LQR control for stall flutter suppression: A polytopic approach*. Issue 1 (July 2017) - Niel, Fabien; Seuret, Alexandre; Zaccarian, Luca; Fagley, Casey
Abstract: In this paper, a robust Linear Quadratic Regulator (LQR) of a NACA 0018 wing with a flap actuator is developed for stall flutter suppression. The nonlinear and switched set of equations of the aeroelastic model is detailed and conveniently expressed as a polytopic uncertain system. A Linear Matrix Inequalities (LMIs) formulation of the LQR problem in the presence of uncertainties is used for the control design. Simulation results confirm the desirable behavior of the arising closed-loop system.